Review on Hollow-Core Fiber Based Multi-Gas Sensing Using Raman Spectroscopy - Qilu Nie; Zhixiong Liu; Mengen Cheng; Shilong Pei; Dexun Yang; Donglai Guo; Minghong Yang (Photonic Sensors)
Abstract In recent years, detecting and quantifying multiple gases have garnered widespread attention across various fields, particularly in volatile organic compound (VOC) detection, which holds significant importance for ecosystems and the medical field. The Raman spectroscopy has been widely used in multi-gas detection due to its advantages in fast response speed and non-destructive detection. This paper reviews the latest research progress of the multi-gas sensing technology in the Raman spectroscopy, focusing on using the hollow-core fiber to enhance the gas signal intensity. The basic principles of the fiber-enhanced Raman spectroscopy are introduced. The detailed discussion includes the system architecture, parameter configuration, and experimental results. Then, the latest advances in the coherent anti-Stokes Raman scattering multi-gas detection technology are reviewed. Finally, the challenges faced by the hollow-core fiber in practical applications are discussed.